Recuperação de larvas infectantes de Trichostrongylus colubriformis em três espécies de gramíneas contaminadas no outono - da Rocha, Raquel Abdallah [UNESP]; Bricarello, Patrizia Ana; da Rocha, Gilberto Pedroso [UNESP]; do Amarante, Alessandro Francisco Talamini [UNESP] (My University, 2012)
This experiment aimed to assess the recovery of infective larvae (L3) of Trichostrongylus colubriformis from Brachiaria decumbens cv. Australiana, Cynodon dactylon cv. Coast-cross and Panicum maximum cv. Aruana. The experimental module comprised six plots, with two plots per herbage species. Larval survival was assessed from autumn to winter, under the effect of two herbage-paring heights (5 and 30 cm). TThe paring was carried out immediately before contamination with faces containing T. colubriformis eggs. The feces and herbage were collected at one, two, four, eight, 12 and 16 weeks after feces had been deposited in the experimental plots. In general, larvae were recovered from both herbage and feces until the 16th week. The longer persistence of these larvae in the environment was probably due to warmer temperatures. The number of L3 recovered from the pasture was not influenced by the height of plants, except for Brachiaria and Aruana herbage in the fourth week. Regarding the concentrations of larvae per kg of dry matter (L3/kg DM), recovery was higher from low pasture in all three herbage species. During the autumn, the development and survival of the T. colubriformis free-living stages were not affected by the different herbage species.
Recovery of Trichostrongylus colubriformis infective larvae from three grass species contaminated in the autumn
Keywords: Epidemiology; Herbages; Nematodes; Sheep; Trichostrongylus colubriformis